Creation of development zones of metathinking with productive or creative writing - Chávez Zamora, Jose M. (2006)
This article presents an instrument to evaluate productive or creative writing at school. The author asumes Vigotsky’s theory about the Zone of Proximal Development (ZPD) in order to develope metathinking with tasks of productive and creative writings.